Word freak : - Fatsis, Stefan (Houghton Mifflin Co., 2001)
Scrabble may be truly called America's game. But for every group of "living-room players" there is someone who is "at one with the board." In Word Freak, Stefan Fatsis introduces readers to those few, exploring the underground world of colorful characters for which the Scrabble game is life-playing competitively in tournaments across the country. It is also the story of how the Scrabble game was invented by an unemployed architect during the Great Depression and how it has grown into the hugely successful, challenging, and beloved game it is today. Along the way, Fatsis chronicles his own obsession with the game and his development as a player from novice to expert. More than a book about hardcore Scrabble players, Word Freak is also an examination of notions of brilliance, memory, language, competition, and the mind that celebrates the uncanny creative powers in us all.